Therapeutic Efficacy of Spencer Technique on Pain and Range of Motion in Frozen shoulder patients: A Randomized Study - Purbia, Neha; Pal, Renuka; Khan, Jafar; Gupta, Sujay; Quershi, Abid R; Menaria, Dinesh (Journal of Neonatal Surgery, 2025)
Background: Frozen shoulder is a musculoskeletal condition represented by painful and restricted shoulder movement which makes a person very weak. Different healing techniques can have varying effects in the management of this condition. This study focuses on exploring the therapeutic efficacy of spencer technique on pain and ROM in frozen shoulder patients. Aim: This study aimed to evaluate the effect of Spencer technique in patients with frozen shoulder. Materials and Methods: This was a randomized study, 20 participants were included for a treatment period of 6 weeks. This group received the Spencer technique. Outcome measures were SPADI (Shoulder Pain and Disability Index) , NPRS (Numeric Pain Rating Scale) and goniometric measurements. Data were analyzed using mean, standard deviation and t-test. Results: The results displayed that the Spencer technique presented better outcomes in reducing the pain and range of motion restoration. Conclusion: The Spencer technique yielded positive effects on functional outcomes, particularly in enhancing joint mobility and reducing disability, which proves to be a beneficial approach